RESPON GURU ATAS IMPLEMENTASI KEBIJAKAN PROGRAM SERTIFIKASI: STUDI PADA KKG DAN MGMP DI KABUPATEN SEMARANG - Yusuf, Amin (Lembaran Ilmu Kependidikan, 2008)
It is important to know the role of the teachers' reaction toward the Certification Program because based on the data we can identify their perception about the program so that we can plan the necessary steps according to the program. This a qualitative research taking as respondents the primay and the secondary teachers joined in the teachers association KKG and MGMP. They were classifiend in 4 categories: (1) those who hah not the 81 degree or still studying to obtain tile degree. (2) those having the S 1 degree with 0-5 year experience. (3) those having the S1 degree with 6-10 year experience. and (4) those who have been certificated. The results showed that they considered the program more as welfare project, . not as aprogram of professional enhancement. Kata Kunci: respon, implementasi kebijakan, dan sertifikasi guruÃ‚Â